(untitled) (Research, Society and Development, 2021)
Sexual harassment in the workplace is a reality that affects many organizations. In many institutions, this type of violence occurs especially when there are power relations and hierarchy involved, and is directly linked to cultural issues, such as sexism and patriarchy, which end up collaborating to cases of violence, very in part interconnected to gender discrimination. This study aims to analyze the incidence of situations that constitute sexual harassment among employees of a Federal University in the interior of Rio Grande do Sul, based on the Model for Evaluating Sexual Experiences proposed by Fitzgerald et al. (1999). For this, a case study of quantitative and descriptive nature was carried out, whose target audience includes the institution’s employees. Data collection was carried out using an online questionnaire, through the institution’s own system, with the participation of 513 employees. The data analysis involved descriptive statistics, using the SPSS 20 software. As a result, it was noticed that most of the employees had never experienced the situations presented in the questionnaire. Despite this, there are cases of sexual harassment occurring against both female and male employees of the institution, but the statistics showed that women are the biggest victims of this form of violence.